The imminent obesity crisis in Asia and the Pacific: First cost estimates - Matthias Helble; Kris Francisco (Asian Development Bank Institute (ADBI), 2017)
Over the past two decades, Asia and the Pacific have not only experienced rapid growth, but in parallel saw a rapid increase in overweight people and obesity. The latest available data indicated that over 40.9% of adults in the region are overweight compared to 34.6% in 1993. It is well documented that obesity and overweight are one of the main risk factors of non-communicable diseases. The rapid spread of excess weight thus implies significant additional costs for health systems and the economy as a whole. Despite the growing significance of this public health problem, we still lack estimates of direct and indirect costs caused by the obesity endemic for the region. This paper fills this gap by providing a first cost estimate for 42 Asia and the Pacific countries. Our estimations include both direct costs caused by additional medical expenditures as well as indirect costs due to higher morbidity and mortality of overweight and obese patients. Overall, our estimates suggest the total costs caused by obesity to be 12% of total health care expenditures or 0.78% of gross domestic product in the region. Obesity is thus a serious threat to the prosperity of the region and calls for urgent action.
Keywords: I15; I19; 330; Cost-of-illness; obesity; overweight; Asia; Pacific